PENGARUH FAKTOR FUNDAMENTAL DAN RISIKO EKONOMI TERHADAP RETURN SAHAM PADA PERUSAHAAN DI BURSA EFEK JAKARTA : Studi Kasus Basic Industry & Chemical - Hardiningsih, Pancawat; Suryanto, L.; Chariri, Ania (JURNAL BISNIS STRATEGI, 2001)
The current research is aimed at analyzing the effect of fundamental factors and economic risk on stock return for industrial and chemical companies listed in the Jakarta Stock Exchanges. Samples used in this research consisted on 30 companies which are observed quarterly from the period of the third quarter 1993 to the third quarter 2000. Data was analyzed by using multiple regression to test the effect of independent variables on dependent variables. F-test and t-test was employed to test the hypotesis with 5% level of significant.The result of investigation showed that fundamental factors and economic risks significantly influenced the stock return. Fundamental factors which were measured by financial ratios, especially return on Assets (ROA) and Price to Book Value (PBV), had a positive effect on stock prices or return. This is because of the fact that the higher these two ratios the better the company's performance end the higher the return. In addition, ROA showed a dominant effect on stock return (this shown by beta standard of 1268). Economic risks which risks which were measured by exchanges rate had negative impact on the return. However, inflation as another proxy of economic risk showed positive influence on stock return. Lastly, the evidence showed that the prediction power of regression model was 42,4%.